Evaluating the impacts of the demerit points system on traffic law violations and driver involvement in road accidents in Israel - Victoria Gitelman; Etti Doveh; Anna Korchatov; Wafa Elias; Shalom Hakkert (European Transport Research Review, 2023)
Abstract Demerit points systems (DPS) have been used in many countries as a means for improving road safety, by monitoring traffic law violations of drivers and applying corrective measures to repeat offenders, while knowledge on their safety impacts is yet incomplete. This study examined the DPS impacts on committing traffic offenses and accident involvement of drivers, in Israel, based on files of the national Licensing Authority and complementary accident files. Models were developed to evaluate changes in violation and accident rates of drivers, who underwent the DPS corrective measures, in after the treatment related to the before period, and accounting for changes observed in the matched comparison-groups. The findings showed that during the three-year period after the measures' implementation, the decrease in committing violations was of 70%, and simultaneously, there was a decrease in drivers' accident involvement, on average, of 1% in severe accidents and of 11% in total injury accidents. The effects were consistent across various groups of drivers by the corrective measures applied and the type of license. The study results support the continued use of the DPS, to improve drivers' behaviors and road safety. To increase its impacts at the national level, the DPS implementation should be supported by stable police enforcement and publicity efforts.